2016
DOI: 10.1038/ncb3326
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα creates elite cells for iPSC reprogramming by upregulating Klf4 and increasing the levels of Lsd1 and Brd4

Abstract: Reprogramming somatic cells into induced pluripotent stem cells (iPSCs) is typically inefficient and has been explained by elite-cell and stochastic models. We recently reported that B cells exposed to a pulse of C/EBPα (Bα' cells) behave as elite cells, in that they can be rapidly and efficiently reprogrammed into iPSCs by the Yamanaka factors OSKM. Here we show that C/EBPα post-transcriptionally increases the abundance of several hundred proteins, including Lsd1, Hdac1, Brd4, Med1 and Cdk9, components of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 71 publications
3
106
0
Order By: Relevance
“…This C/EBPα pulse was also found to efficiently prime cells for subsequent reprogramming to iPS cells [56,57]. During the initial pulse, C/EBPα was found to induce TET2 binding and oxidation of 5mC [57] and to promote active chromatin states at superenhancers near several pluripotency genes [58•]. As with other methods, the efficiency of reprogramming in this system was impaired by knockdown of Tet2 with short hairpin RNAs [58•].…”
Section: Tet Proteins During Induced Differentiation and Reprogrammingmentioning
confidence: 99%
“…This C/EBPα pulse was also found to efficiently prime cells for subsequent reprogramming to iPS cells [56,57]. During the initial pulse, C/EBPα was found to induce TET2 binding and oxidation of 5mC [57] and to promote active chromatin states at superenhancers near several pluripotency genes [58•]. As with other methods, the efficiency of reprogramming in this system was impaired by knockdown of Tet2 with short hairpin RNAs [58•].…”
Section: Tet Proteins During Induced Differentiation and Reprogrammingmentioning
confidence: 99%
“…54,55 A recent study showed that C/EBPa represses the B-cell lineage genes by forming a complex with chromatin-modifying proteins, including LSD1 and HDAC1. 46 Such a mechanism might also be applied in other cell types because progenitors from Cebpa-knockout mice exhibit upregulation of T-cell-related genes, such as Cd7 and Lck, whereas C/EBPa retroviral reintroduction in these progenitors attenuated the expression of these genes to drive myeloid differentiation.…”
Section: -52mentioning
confidence: 99%
“…We have previously reported that C/EBPα can enforce B-cell TF silencing by increasing the expression of the histone demethylase Lsd1 (Kdm1a) and the histone deacetylase Hdac1 at the protein level and that these enzymes are required for the decommissioning of B-cell enhancers and the silencing of the B-cell program (25). Because key B-cell regulators such as Foxo1, Ebf1, and Pax5 are repressed after 3 h of C/EBPα induction (Fig.…”
Section: Resultsmentioning
confidence: 99%